Poor Management of Scabies Among Female Residential Madrasa Students of Bangladesh Caused by Poor Hygiene - Sharmin, Tanjina (The Journal of Ad-din Women’s Medical College, 2025)
Abstract not available The Journal of Ad-din Women's Medical College; Vol. 12 (2), July 2024; p 30-31